Services for Young Children with Disabilities in Romania in the Post-Communist Era - Hartle, Luminita; Quesenberry, Amanda; Doubet, Sharon (Journal of the American Academy of Special Education Professionals, 2020)
In this paper, we will discuss the historical impact of communism on services for children with disabilities in Romania and the efforts made to support young children with disabilities and their families in the post-communist era. The results of the qualitative study focus on attitudes and beliefs of current special education teachers in Romania, and linkages with DEC Recommended practices when envisioning a brighter future for young children with disabilities in Romania.